Immigrant Entrepreneurs: in Search of Identity - Beata Glinka; Agnieszka Brzozowska (Entrepreneurial Business and Economics Review, 2015)
Objective: The purpose of this study is to show identity construction processes of immigrant entrepreneurs and the way these identities are constructed and reconstructed in business and migration experiences. Research Design & Methods: The findings are based on two qualitative research projects on immigrant entrepreneurs: Vietnamese entrepreneurs in Poland and Polish entrepreneurs in the USA. Both studies were based on ethnographic inspiration. Open interviews and observations were used to collect primary data. Findings: The study indicates that identity construction is a process of an interplay of three main elements: being an immigrant, being an entrepreneur, and sense of nationality. This interplay takes place in different, overlapping dimensions: private, social, national and professional, and it takes place in a certain cultural context. Identities of immigrants are constantly constructed and reconstructed in their search for belonging and freedom at the same time. Implications & Recommendations: The results imply that the issue of immigrant entrepreneurship requires open, culturally-oriented and comparative studies. Recommendations for further studies are formulated in the last section of the paper. Contribution & Value Added: The paper provides insight into the processes of migration between different cultural and institutional contexts and their impact on entrepreneurs' identities.